Reshaping Nationalism: CDA of Harari’s Speech, Nationalism in Twenty-First Century - Shafqat Hussain; Abirah Ali Hashmi (ELITE Association Indonesia, 2022)
This research article aims at doing the Critical Discourse Analysis of Yuval Noah Harari’s speech Nationalism in Twenty-First Century. The study follows qualitative method. It is designed descriptively. The study answers the questions that how Harari has treated nationalism, globalization and twenty first century in the speech. Also, it evaluates the discourse techniques proposed by Fairclough. The data were collected from books, YouTube, articles and web links. By using Norman Fairclough’s model of CDA (i.e. description, interpretation and explanation), the data were analyzed and, it was found that nationalism cannot survive alone. A state should also be globalist in order to face the global crisis, as a nationalist state cannot face the annoying music of global crisis: health, nuclear and climate change. The research retains a great importance even at the global level. It has scrutinized the hidden discourse about the existing condition of nationalism which has turned itself as self-centered political entity.